(untitled) (Journal of human and social sciences, 2016)
Divorce is a phenomenon that is almost universal across all human societies, both primitive and advanced alike. It spreads through all forms of life—nomadic, rural, and urban—although its prevalence varies from one society to another depending on prevailing economic, political, and religious circumstances. The individuals most affected by divorce are women and children; divorce is primarily a woman’s problem—rather than a man’s—due to the material, psychological, and social consequences it entails. For a woman who is not employed, divorce means the loss of a vital source of income, namely the husband, who is often the sole provider for the family. In the event of divorce, a woman is compelled to seek another source of income, whether through employment, receiving a basic pension from social security, or by remarrying. In Libya, there has been considerable attention paid to the phenomenon of divorce by the relevant authorities, including the convening of family-related conferences during 1975–1980, as well as efforts by the Ministry of Social Affairs. Furthermore, laws, legislations, and decrees have been issued with the aim of protecting the family, and women in particular, such as Law No. 10 of 1984 on Marriage, Divorce, and Their Effects, and Law No. 16 of 1985 on the Basic Pension, which explicitly granted divorced women a basic pension among other categories. The present study is one of the attempts that focuses on divorced women who receive a basic pension, aiming to determine whether it has been a contributing factor to the recent rise in divorce rates. The findings we reached may provide insights of value to reformers in society, enabling them to address this phenomenon on the basis of scientific research.